Chemical and isotopic composition of high-molecular-weight dissolved organic matter from the Mississippi River plume - Guo, L. D.; White, D. M.; Xu, C.; Santschi, P. H. (Marine Chemistry, 2009)
In order to examine the source and transformation of high-molecular-weight dissolved organic matter (HMW-DOM) in the mixing zone of the Mississippi River plume, HMW-DOM with sizes between 1 kDa and 0.2 mu m was collected along a salinity gradient using cross-flow ultrafiltration. Isolated OM samples were desalted, freeze-dried and characterized for elemental (C and N) and biochemical composition (proteins, carbohydrates and uronic acids), stable isotopic (delta C-13 and delta N-15) and radiocarbon (Delta C-14) signatures, and relative molecular composition using pyrolysis-gas chromatography/mass spectrometry. The organic carbon content of HMW-DOM samples ranged from 31 to 36 wt.%, indicating that isolated colloids are mostly organic in nature. Contents of N ranged from 1.9% to 3.3%, resulting in a C/N ratio of 19-20 at lower salinity stations with a strong influence by terrestrial DOM and 12-15 at higher salinity stations with more freshly photosynthesized marine DOM. While OC-normalized protein contents decreased with increasing salinity, both carbohydrate and uronic acid contents increased with increasing salinity. Variations of pyrograms demonstrated that the proportion of furfural (an indicator of polysaccharides) in HMW-DOM also increased with increasing salinity, while the proportion of phenols decreased with increasing salinity. Changes in carbohydrate, (acid) polysaccharide and phenol contents of HMW-DOM samples reflect the variation in DOM sources along the salinity gradient, with higher phenol and low polysaccharide contents in lower salinity areas but higher polysaccharide and low phenol contents in coastal waters. Values of delta C-13 increased from -25.24 parts per thousand at the Mississippi River fresh water end-member station to -21.86 parts per thousand at an offshore station in the Gulf of Mexico. Changes in stable isotope composition resemble the changes in molecular composition from freshwater to coastal waters. Values of delta N-15, on the other hand, varied little, from 3.5 parts per thousand to 4.9 parts per thousand without a consistent trend, indicating that delta N-15 is a less sensitive source tracer. Measured radiocarbon signatures (Delta C-14) expressed as apparent C-14 ages ranged from > modern at lower salinity stations to 400-800 y BP at coastal stations. Results of isotopic mass balance revealed that, in addition to end-member organic matter from river and marine sources, at least 10-25% of the HMW-DOM could derive from reworked or regenerated DOM in the Mississippi River plume, most likely through sediment-water interactions and lateral transport. Thus, reworking processes are important in governing the chemical and isotopic composition of DOM in the estuarine mixing zone. (C) 2009 Elsevier B.V. All rights reserved.
id: 1827; 465CM Times Cited:1 Cited References Count:51Y